HUBUNGAN ASUPAN PROTEIN HEWANI DAN NABATI DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER 3 DI DESA DAWUHAN: The Relationship Between Animal and Vegetable Protein Intake with The Incidence of Anemia in 3rd Trimester Pregnant Women in Dawuhan Village - Meilinda Ulfiatus Soleha (Forind Press, 2024)
Anemia is an event where the body has too few red blood cells (erythrocytes), where red blood cells contain hemoglobin (Hb) which functions as a carrier of oxygen throughout the body's tissues. Anemia in pregnancy cannot be separated from the physiological changes that occur during pregnancy, the age of the fetus, and the condition of the previous pregnant woman, so it is necessary to pay attention to the intake of protein and other nutrients. The purpose of this study was to analyze the corellation between animal and vegetable protein intake and the incidence of anemia in third trimester pregnant women in Dawuhan village. This study used a correlational analysis design with a cross-sectional approach the data were analyzed by computer with the Spearman test p value: 0.05. The results showed that 28 respondents had less animal and vegetable protein intake, 27 pregnant women who experienced anemia. Spearman rank test results with p value: 0.000. The conclusion of the study is that there is a corellation between animal and vegetable protein intake and the incidence of anemia in third trimester pregnant women in Dawuhan village (p = 0.000 <0.05). The suggestions put forward are the need for education and outreach to pregnant women, families and husbands about diet and myth facts about food during pregnancy through home visits in the healthy family program.